The Cost of Toxicity in Microalgae: Direct Evidence From the Dinoflagellate Alexandrium - Blossom, Hannah E.; Markussen, Bo; Daugbjerg, Niels; Krock, Bernd; Norlin, Andreas; Hansen, Per Juel (Frontiers in Microbiology, 2019)
Empirical evidence of the cost of producing toxic compounds in harmful microalgae is completely lacking. Yet costs are often assumed to be high, implying substantial ecological benefits with adaptive significance exist. To study potential fitness costs of toxin production, sixteen strains including three species of the former Alexandrium tamarense species complex were grown under both carbon limitation and unlimited conditions. Growth rates, levels of intracellular paralytic shellfish poisoning toxins (PSTs) and effects of lytic compounds were measured to provide tradeoff curves of toxicity for both PST and lytic toxicity under high light (300 µmol photons m-2 s-1) and under low light (i.e. carbon limited; 20 µmol photons m-2 s-1). Direct fitness costs in terms of reduced growth rates with increasing PST content were evident under unlimited conditions, but not under carbon limitation, in which case PST production was positively correlated with growth. The cost of production of lytic compounds was detected both under carbon limitation and unlimited conditions, but only in strains producing PST. The results may direct future research in understanding the evolutionary role and ecological function of algal toxins. The intrinsic growth rate costs should be accounted for in relation to quantifying benefits such as grazer avoidance or toxin-mediated prey capture in natural food-web settings.